Analisis Komparasi Kinerja Perbankan Syariah Sebelum dan Pasca Covid-19 - Samy Abiyyu; Sri Cahyaning Umi Salama; Fitrian Aprilianto (FEB Universitas Sultan Ageng Tirtayasa, 2025)
This study compares the performance of Bank Muamalat Indonesia and Bank Panin Dubai Syariah before and after the Covid-19 pandemic using the CAMEL analysis and Paired T-Test. The results show that Bank Muamalat experienced an increase in the CAR ratio during the pandemic, followed by a slight decline post-pandemic, while Panin Dubai Syariah showed more fluctuating CAR trends. In terms of NPF, Bank Muamalat showed asset quality improvement, whereas Panin Dubai Syariah faced a slight increase in credit risk. Other indicators such as BOPO and NPM also varied across both banks. These findings highlight the influence of internal and external factors on Islamic banks' performance and underscore the importance of adaptive strategies in responding to economic changes